Quality Control in Breast Tomosynthesis (Brazilian Journal of Radiation Sciences (BJRS), 2015)
In Brazil, breast cancer is the most common and the leading cause of death among women, with estimated 57,000 new cases in 2014. The mammography (2D) plays an important role in the early detection of breast cancer, but in some cases can be difficult to detect malignant lesions due overlap of breast tissues. The Digital Breats Tomosynthesis (DBT: 3D) reduces the effects of overlap, providing improved characterization of mammographic findings. However, the dose may double as compared with mammography. This study presents results of Contrast to Noise Ratio (CNR) and image quality evaluation on Siemens mammography equipment Mammomat Inspiration with tomosynthesis. The CNR was determined with Polymethylmethacrylate (PMMA) layers of 20 to 70 mm thick and an aluminum foils of 0,2 mm thickness and area of 10 mm². Image quality was assessed with the ACR Breast Simulator. In the evaluation of image quality, the detectability of fibers and masses was identical in 2D and 3D systems. Displaying fibers were 4,5 and 4 mass in both modes. In 2D mode were identified 3,5 microcalcifications groups, and 3D showed 3 groups. The Mean Glandular Dose (MGD) for the simulator in 2D mode was 1,17 mGy and 2,35 mGy for the 3D mode. The result reinforces the importance of quality control in the process of obtaining the images and obtained in accordance CNR values, ensuring image quality and compatible dose in 2D and 3D processes.